COMMONLY PRACTICED RASAYOGAS IN SHEETAPITTA W.S.R. TO URTICARIA: A REVIEW - M.M Nidhin; Nambiar Sruthi; Sharma Govinda K; Balagopalan Devika (International Journal of Applied Ayurved Research, 2018)
Sheetapitta is one among the Tvak Vikara that have similar hetu of kotha and udarda. Vata and Kapha are two “Doshas”, which are primarily disturbed which in turn is associated with Pitta resulting in tridosha prakopa leading to redness, swelling itching on the skin etc. Symptoms include appearance of wheals all over the body with severe itching, burning sensation and pain. Symptomatology and causative factors of Sheetapitta can be considered similar to that of ‘Urticaria’. In this work an attempt was made to collect the details of Rasayogas used in Sheetpitta. Method adopted was, review of literatures in print and digital media. In total 17 formulations were enlisted among which 10 formulations are directly indicated in Sheetapitta and 7 formulations are commonly prescribed by the physicians in the disease. Attempts to analyze the mode of action of these formulations based on their ingredients and efficacy at the level of dosha, samprapthi and symptoms has been done in this article.